Moderating Role of Stakeholders Attributes on Implementation of Rural Electrification Projects in Kenya (Global Journal of Management and Business Research, 2020)
Stakeholders strongly influence the outcome of projects especially in complex projects with heterogeneous stakeholders, thus understanding their influence is essential to ensure project success and attainment of objectives. The benefits of rural electrification range from lighting, access to information, improved study environment for school children as well as improved businesses which in turn create employment opportunities and contribute to development and poverty reduction. This study sought to examine the role of stakeholders in the implementation of rural electrification projects in Kenya. The study focused on project risk management, planning, leadership, monitoring, and control roles with a moderating role of stakeholders' attributes in the implementation of rural electrification projects in Kenya. The research targeted rural electrification projects implemented by the Kenya government in public primary school. The key respondents of the study were project managers of all the implemented projects.
Keywords: project risk management; project planning; project leadership